Training to failure and beyond in mainstream resistance exercise programs - Willardson, J.; Norton, L.; Wilson, G. (Strength and Conditioning Journal, 2010)
INTENTIONALLY REACHING FAILURE DURING RESISTANCE EXERCISE SETS IS A COMMON PRACTICE THAT MIGHT BE MOST BENEFICIAL FOR STIMULATING HYPERTROPHY. HOWEVER, FAILURE TRAINING PERFORMED TOO FREQUENTLY CAN RESULT IN REDUCTIONS IN THE RESTING CONCENTRATION OF TESTOSTERONE AND CONTRIBUTE TO THE OVERTRAINING SYNDROME. THE RESEARCH SUGGESTS THE GREATEST EFFECTIVENESS WHEN FAILURE TRAINING IS PRACTICED CONSISTENTLY OVER 6-WEEK CYCLES, INTERSPERSED WITH EXCLUSIVE NONFAILURE TRAINING CYCLES OVER EQUAL PERIODS. COACHES SHOULD CONSIDER ATHLETES' TRAINING STATUS AND GOALS AND THE POINT IN A YEARLY TRAINING CYCLE TO DETERMINE WHETHER SETS ARE TO BE PERFORMED TO FAILURE OR ENDED SHORT OF REACHING FAILURE.